Changes in the population and functional profile of bacteria and fungi in the rhizosphere of Suaeda salsa is driven by invasion of Spartina alterniflora. (November 2022) - Yu, Chengfeng; Cao, Jicheng; Du, Wen; Zhu, Zhiyong; Xu, Min
Graphical abstract: Highlights: EC and NO3 − -N were found to significantly influence the microbial communities. Tenericutes, Firmicutes, Proteobacteria and Actinobacteria are more sensitive. The Suaeda salsa rhizosphere fungal pathogens increased greatly after plant invasion. Abstract: Changes in rhizosphere microbial populations and their functions in response to Spartina alterniflora root invasion could potentially reveal part of the mechanism of Suaeda salsa degradation. In this study, rhizosphere soils were collected from regions where S. alterniflora (SA) and S. salsa (SS) grew independently as well as rhizosphere soil from mixed growth regions (namely MSA and MSS) before applying high-throughput sequencing technology to study the characteristics of microbial communities. The results showed that the physicochemical properties of the rhizosphere soils were different between the groups of samples. However, based on the multi-factor PERMANOVA analysis, only EC and NO3 − -N were found to significantly influence the microbial communities' composition. Furthermore, α diversity indices and β diversity analyses revealed that the diversity and structure of rhizosphere microbial community changed in varying degrees after invasion. Compared with SS, the most abundant bacteria phylum namely Tenericutes, Firmicutes, Proteobacteria and Actinobacteria in MSS were identified as major species that increased significantly in abundance in response to S. alterniflora root invasion, while the composition of fungal community did not change. Furthermore, PICRUSt analysis revealed that the higher abundance of signal transduction, membrane transport, cell motility and certain disease-related functional pathways of MSA and MSS could be conducive to the colonization and survival of bacterial pathogens. Additionally, the analysis of the FUNGuild database confirmed that a higher proportion of pathotroph and pathogen. This could very likely cause S. salsa to be more susceptible to soil pathogenic fungi in mixed growth region. In contrast, the increase of the saprotroph-symbiotroph could be beneficial for the colonization and expansion of S. alterniflora . This study provides a new perspective for elucidating the driving mechanism by microorganisms behind S. salsa 's degradation following S. alterniflora 's invasion.